2021
DOI: 10.1111/radm.12476
|View full text |Cite
|
Sign up to set email alerts
|

Design principles of hybrid approaches in new product development: a systematic literature review

Abstract: Setting the right approach for new product development (NPD) in the presence of uncertainty remains an ongoing debate in innovation management. Stage‐gate systems (SGS) and agile methodology (AM) are the dominant approaches. Recently, hybrid approaches (combining SGS and AM) have been proposed. Although these hybrid approaches represent a significant development in NPD, combining them without considering their design principles might lead to contradictory and competing conceptual formulations, thus increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…, 2020) with different paces (agile and slow), Phased Learning Performance depicts more complex PMMS. Our findings indicate that firms adopted agile experimentation (Gomes et al. , 2022b) within an ecosystem and, consequently, set their PMMS to measure and manage performance in short and long cycles of testing, measuring and learning.…”
Section: Discussionmentioning
confidence: 92%
“…, 2020) with different paces (agile and slow), Phased Learning Performance depicts more complex PMMS. Our findings indicate that firms adopted agile experimentation (Gomes et al. , 2022b) within an ecosystem and, consequently, set their PMMS to measure and manage performance in short and long cycles of testing, measuring and learning.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, evidence shows risks leading to new product development failures, such as grouping different forms of excessive product development, from scope creep to over specification and feature creep (Marzi, 2022). Also, not considering agile methodologies or hybrid models (Gomes et al, 2022), and the role of institutional factors, especially in the context of emerging economies (Bao, Su, & Noble, 2021), could be relevant. In any case, the literature on the New Product Development Process (NPDP) has been a dominant approach traditionally, and deeply influences the practice and research (Salvato & Laplume, 2020).…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Third, because there may be other factors that have not been included in the model, future research should corroborate the results in specific contexts, such as the service sector and at regional levels in a country. Finally, other approaches can be useful to analyze the new product development process in future research, such as the New Product Development Ability (Panizzon, Milan, Dorion, & Munhoz Olea, 2021) or hybrid approaches (Gomes et al, 2022).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, despite the magnitude of the OVF phenomenon, it has received little attention, especially outside the software development domain (Shmueli & Ronen, 2017), and recent literature has only highlighted the relevance of OVF to physical products and services (Cesaretto et al, 2021;De Giovanni, 2019;Jain, 2019;Liu & Yu, 2017). Consequently, the nature, origins and outcomes of OVF remain understudied and have not been appropriately recognised and encompassed in the NPD literature (de Vasconcelos Gomes et al, 2021;Gyimah et al, 2019). An analysis of the available studies showed that the body of knowledge related to OVF is poorly theoretically developed, and terminological confusion is widespread.…”
Section: Introductionmentioning
confidence: 99%